On discouraging environments in team contests: Evidence from top-level beach volleyball - Hendrik Sonnabend (Managerial and Decision Economics, 2020)
This contribution empirically investigates the adverse effects of unbalanced competition and negative feedback in team contests in the field. Using a unique data set sourced from top-level beach volleyball, I provide evidence for discouragement effects in line with contest theory. The analysis identifies a non-linear relationship between ex ante contestant heterogeneity and performance. Overall, no gender differences can be found. Finally, it shows that age diversity in teams helps to overcome setbacks.
Keywords: 650